Mechanical performance of PEEK-Ti6Al4V interpenetrating phase composites fabricated by powder bed fusion and vacuum infiltration targeting large and load-bearing implants. (March 2022) - Chen, Xu; Wu, Yanlong; Liu, Huilong; Wang, Yaning; Zhao, Guangbin; Zhang, Qingxian; Wang, Fu; Liu, Yaxiong
Graphical abstract: Highlights: PEEK-Ti6Al4V composites were developed using powder bed fusion and vacuum infiltration. PEEK-Ti6Al4V composites had higher compressive and flexural strengths than the Ti6Al4V lattices of equivalent elastic moduli. PEEK-Ti6Al4V composites exhibited higher fatigue strength than the Ti6Al4V lattices of equivalent elastic moduli. The enhancing mechanisms can be the alleviation of strut deformation and the resistance to crack propagation. Abstract: Comprehensive mechanical properties (high strength, good fatigue resistance and tunable stiffness) are significant for large and load-bearing implants, but still remain a challenge in practical applications. Polyetheretherketone (PEEK)-Ti6Al4V interpenetrating phase composites (IPCs) with comprehensive mechanical properties were developed using a two-step process: fabricating Ti6Al4V microlattices using powder bed fusion (PBF) and subsequently manufacturing PEEK-Ti6Al4V IPCs using vacuum infiltration. The strut defects in the Ti6Al4V microlattices induced by PBF process were filled with PEEK, and thus excellent interfacial connection was achieved. Mechanical tests, under both quasi-static loading conditions (compression and three-point bending conditions) and dynamic loading condition (three-point bending condition), were carried out on the PEEK-Ti6Al4V composites with low and high modulus (20.0 and 60.0 vol% Ti6Al4V) and the bare Ti6Al4V microlattices of equivalent elastic moduli. It was found that the composites had higher compressive and flexural strengths than the lattices. Moreover, the composites exhibited higher fatigue strength and longer fatigue life than the lattices. The fracture behaviors and the FEM simulation results revealed that the enhancing mechanisms for the PEEK-Ti6Al4V composites can be the alleviation of strut deformation and the resistance to crack propagation. Thus, the PEEK-Ti6Al4V composites can be promising materials for large and load-bearing implants.